2009
DOI: 10.1140/epjb/e2009-00410-2
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy excitations in the three-dimensional random-field Ising model

Abstract: Abstract. The random-field Ising model (RFIM), one of the basic models for quenched disorder, can be studied numerically with the help of efficient ground-state algorithms. In this study, we extend these algorithm by various methods in order to analyze low-energy excitations for the three-dimensional RFIM with Gaussian distributed disorder that appear in the form of clusters of connected spins. We analyze several properties of these clusters. Our results support the validity of the droplet-model description fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 73 publications
2
16
0
Order By: Relevance
“…This is because around the transition region many domain wall rearrangements are possible (with very small energy difference) leading to high number of excitations. Such a situation was also observed in 3d RFIM [45]. At higher disorders spin orientation are dominated by the {φ i }, which is fixed for all configurations at each W here.…”
Section: Density Of Statessupporting
confidence: 76%
“…This is because around the transition region many domain wall rearrangements are possible (with very small energy difference) leading to high number of excitations. Such a situation was also observed in 3d RFIM [45]. At higher disorders spin orientation are dominated by the {φ i }, which is fixed for all configurations at each W here.…”
Section: Density Of Statessupporting
confidence: 76%
“…Such excitations have been studied in d = 3 so far. 30 Hence, for each realization {hε i } of the disorder, we obtained seven different (ground-state) configurations for different types of boundary conditions/constraints [PBC, (++), (−−), (+−), (−+), bulk-induced droplets, and singlespin-induced droplets]. Technically, to obtain the droplets, we extracted the absolute differences between the spin configuration of two or more GSs via linear combinations of the configurations.…”
Section: Domain Walls and Droplet Excitationsmentioning
confidence: 99%
“…Instead, for the third approach, we follow the arguments of Ref. 30. Therein, it is shown that the distribution of single-spin-induced droplet radii scales as p(R) ∼ R −θ .…”
Section: Domain Walls and Droplet Excitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…p = 1/N was chosen since it is the percolation threshold, i.e., the graph is a forest like structure and to form a cycle almost surely non existent edges, i.e., distance 2, need to be used. Like other studies on the solution space structure of different optimization problems, we look at excitations [34][35][36]. To detect signatures of RSB, we use a criterion introduced in the context of TSP by Mézard and Parisi in Ref.…”
Section: Introductionmentioning
confidence: 99%